Microfluidic-based ion-selective thermoplastic electrode array for point-of-care detection of potassium and sodium ions - Ozer, Tugba; Henry, Charles S. (SPRINGER WIEN, 2022)
A microfluidic paper-based thermoplastic electrode (TPE) array has been developed for point-of-care detection of Na+ and K+ ions using a custom-made portable potentiometer. TPEs were fabricated using polystyrene as the binder and two different types of graphite to compare the electrode performance. The newly designed TPE array embedded in a polymethyl methacrylate chip consists of two working electrodes modified with carbon black nanomaterial and an ion-selective membrane, and an all-solid-state reference electrode modified with Ag/AgCl ink and poly(butyl methacrylate-co-methyl methacrylate) membrane via drop-casting. Ion-selective membrane compositions and conditioning steps were optimized. Under optimized conditions, ion-selective TPEs demonstrated fast response time (4 s) and good stability. The TPE array demonstrated a Nernstian behavior for K+ with a sensitivity of 59.2 +/- 0.2 mV decade(-1) and near-Nernstian response for Na+ with a sensitivity of 54.0 +/- 1.1 mV decade(-1) in the range 10(-1) -10(-4) M and 1- 10(-3) M, respectively. The detection limits were 1 x 10(-5) M and 1 x 10(-4) M for K+ and Na+, respectively. In addition, a K+ and Na+ selective microfluidic paper-based analytical device (mu PAD) was applied to artificial serum analysis and found in good agreement with average recoveries of 101.3% and 99.7%, respectively, suggesting that the developed ISE array is suitable for detection of sodium and potassium in complex matrix.
Keywords: Microfluidic; Paper-based chip; Ion-selective electrode; Carbon nanomaterial; Point-of-care devices; Potentiometric detection; PAPER-BASED DEVICE; CYSTIC-FIBROSIS; CARBON; SWEAT; POLYMER; SENSORS; STABILITY; DESIGN; Chemistry